1994
DOI: 10.2307/1131282
|View full text |Cite
|
Sign up to set email alerts
|

Children's Understanding of Knowledge Acquisition: The Tendency for Children to Report That They Have Always Known What They Have Just Learned

Abstract: Children's attention to knowledge-acquisition events was examined in 4 experiments in which children were taught novel facts and subsequently asked how long they had known the new information. In Experiment 1, 4- and 5-year-olds tended to claim they had known novel animal facts for a long time and also reported that other children would know the novel facts. This finding was replicated in Experiment 2, using facts associated with chemistry demonstrations. In Experiments 3 and 4, children were taught new color … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
158
1
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(173 citation statements)
references
References 17 publications
12
158
1
2
Order By: Relevance
“…O'Neill et al (1992) report that at this age children come to understand which sense organ to use in order to find out the weight (use hand to lift object) or the color of an object (use eyes to look at it): modality-specificity test. Similarly, Taylor et al (1994) found that between 4 and 6 years, children become able to distinguish between words (e.g., animal or color names) that they have learned recently (e.g., maroon) and those they have known for some time (e.g., red): When-learned test. Also within that age bracket (e.g., Sodian and Wimmer 1987) children become able to distinguish knowledge (success in finding an object after seeing where it was put) from a lucky guess (success in finding the object without having seen where it was put): know-guess distinction.…”
Section: Understanding the Causal Link Between Mental Statesmentioning
confidence: 92%
See 3 more Smart Citations
“…O'Neill et al (1992) report that at this age children come to understand which sense organ to use in order to find out the weight (use hand to lift object) or the color of an object (use eyes to look at it): modality-specificity test. Similarly, Taylor et al (1994) found that between 4 and 6 years, children become able to distinguish between words (e.g., animal or color names) that they have learned recently (e.g., maroon) and those they have known for some time (e.g., red): When-learned test. Also within that age bracket (e.g., Sodian and Wimmer 1987) children become able to distinguish knowledge (success in finding an object after seeing where it was put) from a lucky guess (success in finding the object without having seen where it was put): know-guess distinction.…”
Section: Understanding the Causal Link Between Mental Statesmentioning
confidence: 92%
“…These results were partially replicated 1 by Naito (2003) on a Japanese sample. She also found a relationship between free recall and children's ability to understand when they had learned a fact (Taylor et al 1994). 2 In a recent study (Perner et al in press) we used a new measure of episodic remembering, contrasting free recall of experienced events, which can in principle be episodically remembered, with recall of indirectly conveyed events, which can in principle not be remembered, only known.…”
Section: Understanding the Causal Link Between Mental Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…In both studies, it is as if once children knew what the whole picture looked like, they were unable to take the perspective of someone who had never seen the whole picture. In a third study, Taylor, Esbensen, and Bennett (1994) found that, moments after being taught a novel fact, 4 and 5-year-olds claimed to have known that fact for a long time. In other words, children tended to report to have always known a piece of information that they had just learned.…”
Section: Knowledge Acquisitionmentioning
confidence: 96%